ANALISIS INDEKS PENERAPAN ANTI-KORUPSI DAN BUDAYA ETIKA DI INDUSTRI INDONESIA - Riduan Siagian; Parlaban Karo-Karo; Nur Maliana Harum HRP (Jurnal Industri Kreatif dan Inovatif, 2025)
This study analyzes the index of anti-corruption policy implementation and ethical culture in Indonesia’s industrial sector. Corruption remains a serious problem that negatively affects not only national economic performance, but also public trust in both governmental and private institutions. Since the post-1998 reform era, anti-corruption efforts have shifted from law enforcement–centered approaches toward building integrity through institutional reform and strengthening organizational culture. Using a literature review approach with qualitative document analysis, the research integrates institutional theory and organizational culture theory (Schein) to organize findings related to regulations, organizational values, and changes in internal behavior. The study finds that the effectiveness of anti-corruption policies is strongly shaped by institutional reform, ethical leadership, the implementation of integrity programs (e.g., Integrity Zone), and the sustainability of cultural transformation. Evaluation through indicators such as SPI, IPAK, and IPK suggests improvements in some areas, yet significant gaps still remain. Strategic recommendations include adopting information technology to enhance monitoring and reporting transparency, conducting continuous anti-corruption training and ethics education, and strengthening cross-institution and stakeholder collaboration to address both structural and cultural barriers in the industry.